Generation Z's Perception of the Preservation of the Sasak Script - Ginanda Azahra Va Arni; Umar; Arif Widodo (LEGAL BRIEF, 2022)
This study aims to determine the perception of generation Z on the preservation of Sasak characters. The research respondents considered 25 people aged 14-22 years. This research is designed in quantitative quantitative form. Data collection using a questionnaire and the results of the questionnaire were analyzed using descriptive statistics. The results showed that the interest in creating Z in preserving the Sasak script was quite high but it made Z difficult to preserve the Sasak script because he only learned it in elementary school (SD). Generation Z has minimal knowledge and skills as well as limited access in developing Sasak characters. Sasak script preservation program needs to get attention and support from the government and society in order to create Z's access to learn, develop, and be able to preserve Sasak script.